Haptic Ring Interface Enabling Air-Writing in Virtual Reality Environment - Yeom, Kiwon; You, Bum-Jae; Maeng, JooHyun; Kwon, Jounghuem (2015 IEEE International Symposium on Mixed and Augmented Reality, 2015)
We introduce a novel finger worn ring interface that enables complex spatial interactions through 3D hand movement in virtual reality environment. Users receive physical feedback in the form of vibrations from the wearable ring interface as their finger reaches a certain 3D position. The positions of the fingertip are extracted, linked, and then reconstructed as a trajectory. This system allows the wearer to write characters in midair as if they were using an imaginary whiteboard. User can freely write in the air using Korean characters, English letters, both upper and lower case, and digits in real time with over 92% accuracy rate. Thus, it is now conceivable that anything people can do on contemporary touch based devices, they could do in midair with a pseudocontact interface.